Effect of inclined thick fin on natural convection in a cavity heated from bottom - Varol, Yasin; Özgen, Filiz (My University, 2015)
In this study, natural convection heat transfer in a square cavity with an adiabatic fin mounted on a vertical wall was investigated numerically. Vertical boundaries were adiabatic and horizontal boundaries were isothermal at different constant temperature. Two-dimensional equations of conservation of mass, momentum and energy were solved using finite difference method. Successive under relaxation (SUR) method was used to solve linear algebraic equations.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Doğal Taşınım; Kanatçık; Kare Geometri